Efeitos da temperatura e da contaminação de rejeitos da mineração no crescimento e na fisiologia de Ricciocarpos natans (L.) Corda - Gimenes, Luana Lorca Sartoris (2020)
In recent years, the contamination of Brazilian water resources by metals contained in mining waste has become frequent and, in addition, another environmental factor that must also be considered, concomitantly, is the increase in the global temperature of the planet caused by global warming. In this context, this work aimed to evaluate the toxicity of three metals (Al, Mn and Zn) in bioassays containing different concentrations of individual metals and in combinations in the growth in biomass and width and in the physiological responses of Ricciocarpos natans under two temperatures, in addition to evaluate the growth and physiological changes of individuals exposed to water contaminated by mining waste, and to evaluate the percentage of removal efficiency of metals from the test solution. Samples of water contaminated by mining waste from the dam burst in Mariana (MG) in 2015 were collected and the metals determined. The treatments included healthy individuals of R. natans (n = 10, ± 0.5 cm wide) exposed for 30 days (5 repetitions), 12/12 photoperiod, to the metal concentrations found in the tailings (Al = 1.5 mg L-1; Mn and Zn = 0.7 mg L-1) and in two higher concentrations (Al = 2.5 and 5.0 mg L-1; Mn and Zn = 1.5 and 3.0 mg L- 1) at temperatures of 25 ºC and 27 ºC. Twice a week, the plants of all treatments had their fresh masses determined gravimetrically and the width measured. The fresh masses accumulated from the macrophytes during the sampling period were adjusted to the logistic model. Physiological analyzes of photosynthetic pigments (chlorophyll-a, chlorophyll-b, carotenoids), antioxidants (anthocyanin and flavonoid) and oxidative stress (lipid peroxidation and electrolyte leakage) were performed once a week. The growth and physiological responses of the macrophyte R. natans were affected by exposure to the concentrations of the metals Al, Mn and Zn. The growth coefficients and the doubling time changed with the addition of the metals. The growth kinetics for the mixture of metals indicated that the higher the combined concentrations, the greater the damage to the growth and physiology of the macrophyte, as necrosis in plant tissues occurred faster. In water contaminated by the tailings, the individuals of R. natans also showed impaired growth since the beginning of the experiments. The increase in temperature by 2 ° C (27 ° C) together with exposure to metals negatively influenced the growth of R. natans, since for most of the bioassays it was not possible to observe an increase in biomass or even width. In general, metals inhibit plant growth by around 50% of biomass production. The present study contributes to the understanding of the impacts that can occur by metals contained in mining tailings and the increase in temperature in aquatic ecosystems in the growth and physiology of aquatic macrophytes.